Influence of Aberrations on Modal Decomposition for LMA Fiber Laser Systems - Chai, Junyu; Liu, Wenguang; Zhang, Jiangbin; Xie, Kun; Lu, Yao; Li, Changjin; Liu, Pengfei; Zhou, Qiong; Jiang, Zongfu; Zhao, Guomin (Frontiers in Physics, 2022)
Understanding the mode components is of great importance to manipulate the optical modes and to improve the optical system performance. However, various forms of aberrations, stemming from misalignment, imperfect optical components and system design, degrade the performance of the modal decomposition (MD) system. Here, we analyze the influence of various Zernike aberrations on the MD performance in the large mode area (LMA) fiber laser systems. Using computer generated optical correlation filter (OCF) together with the angular multiplexing technique, we can simultaneously measure multi-modal contents. Among the common aberrations, we find that the MD results is least sensitive to vertical astigmatism aberration. However, the vertical coma aberration and horizontal coma aberration have large impact on MD results under the same aberration strength, which show rather large change in the modal weight and intermodal phase. Our analysis is useful to construct the precise MD system, applicable for high-power optical fiber modal analysis and mode control.